Synthesis and Photoluminescent Properties of Li2SrSiO4:Pb2+ - BAŞAK, ALİ SADİ (SPRINGER, 2014)
Pure and Pb2+ doped Li2SrSiO4 materials were synthesized at 900A degrees C for 12 h in air. The phases of the synthesized materials were determined by X-ray powder diffraction (XRD). The photoluminescence properties of the synthesized phosphors were investigated by spectrofl uorometry at room temperature. The emission and excitation bands of Li2SrSiO4:Pb2+ were observed at 381 and 271 nm, respectively. The dependence of the emission intensity on Pb2+ concentration for Li(2)Sr(1-x)PbxSiO(4) was studied in detail. It was observed that the optimum concentration of Pb2+ in Li2SrSiO4 is 0.01 mol.%. The Stokes shifts of Li2SrSiO4:Pb2+ phosphor was calculated to be 10653 cm(-1).
Keywords: silicate phosphors; luminescence; X-ray powder diffraction; LUMINESCENCE PROPERTIES; EMITTING PHOSPHOR; ENERGY-TRANSFER; PB2+; EU2+; IONS; CE3+